Preparation, structure and properties of octenylsuccinic anhydride modified starch - Bai, Yanjie (Kansas State University, 2013)
The reaction of starch and octenylsuccinic anhydride (OSA) produces lipophilic starch that has the ability to stabilize oil-in-water emulsions. The functional properties of octenylsuccinate (OS) starch depend on its molecular structure and distribution of OS groups. Structures of OSA and OS starches were investigated by NMR spectroscopy. In granular OS starches, OS groups were substituted at O-2, O-3 positions, but not the O-6 position. Distribution of OS groups was investigated by enzyme hydrolysis followed by chromatography analysis. OS substitution predominantly occurred at the amorphous region of the starch granules. OS starch of degree of substitution (DS) 0.018 had OS groups located close to the branching points, whereas the OS substitution in OS starch of DS 0.092 occurred near non-reducing ends as well as the branching points. OS starches with different substitution patterns were prepared from two approaches. OS starches from the first approach had OS substitution near the branching points or non-reducing ends, whereas OS starches from the second approach had OS groups distributed randomly throughout the starch chains. A method of preparing OS starch by dry heating a mixture of waxy maize starch and OSA was developed. The optimum reaction was investigated and found to be pH 8.5 by addition of 3% NH4HCO3, 180 °C and 2 h. Reaction efficiency of ca. 90% was obtained at OSA levels from 1 to 6%. The OS starch had a DS of 0.0202 with 98% solubility when reacted with 3% OSA. Transglucosidation occurred during the reaction. The OS starch had a degree of branching of 19.8 %. The highly debranched OS starch showed excellent emulsification property for vitamin E and vitamin A. The structural changes of insoluble native waxy maize starch granules to cold watersoluble pyrodextrin during dextrinization under acidic conditions were investigated. We proposed that the starch was hydrolyzed by acid in the amorphous regions. Unwinding of the double helices also occurred, and crystallite size decreased. Starch molecules were hydrolyzed into small molecule fractions but remain in a radial arrangement. Glycosyl linkages including - (1 2), -(1 6), -(1 2), and -(1 6) linkages were formed and the majority starch chain terminals were 1,6-anhydro- -D- lucopyranose. Transglucosidation occurred during dextrinization and the resulted pyrodextrin was highly branched.
Keywords: Starch; Octenylsuccinate anhydride; Emulsion